Coyote America : a natural and supernatural history - Flores, Dan L. (Dan Louie), 1948- (Basic Books, a member of the Perseus Books Group, 2016)
This book "is both an environmental and a deep natural history of the coyote. It traces both the five-million-year-long biological story of an animal that has become the wolf in our backyards, as well as its cultural evolution from a preeminent spot in Native American religions to the hapless foil of the Road Runner. A deeply American tale, the story of the coyote in the American West and beyond is a sort of Manifest Destiny in reverse, with a pioneering hero whose career holds up an uncanny mirror to the successes and failures of American expansionism"--Dust jacket flap.